2014
DOI: 10.17221/7780-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and assessment of electrospun Poly/hydroxyapatite nanofibres together with a cell adhesive for bone repair applications

Abstract: ABSTRACT:In this study, we fabricated Poly(lactide-co-glycolide)/hydroxyapatite (PLGA/HAp) nanofibres using electrospinning and evaluated their potential use for bone repair applications. Analysis confirmed that the PLGA nanofibres were similar to the natural extracellular matrix and included HAp particles. Further, gelatin augmented the adhesion of electrospun nanofibres in the cell adhesion test. Therefore, electrospun PLGA/HAp nanofibres together with gelatin can be utilised for bone repair applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…In our previous study conducted to assess cell adhesion to PLGA/HAp nanofibres with gelatin, we identified PLGA/HAp nanofibres in 1% and 2% gelatin that were counterstained with haematoxylin, indicating cell adhesion to the nanofibres, and demonstrating that gelatin is suitable for use for cell adhesion to electrospun nanofibres (Heo et al 2014). Previous studies with PLGA/HAp nanofibres have attempted to assess cell seeding and viability.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In our previous study conducted to assess cell adhesion to PLGA/HAp nanofibres with gelatin, we identified PLGA/HAp nanofibres in 1% and 2% gelatin that were counterstained with haematoxylin, indicating cell adhesion to the nanofibres, and demonstrating that gelatin is suitable for use for cell adhesion to electrospun nanofibres (Heo et al 2014). Previous studies with PLGA/HAp nanofibres have attempted to assess cell seeding and viability.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous in vitro studies have demonstrated the potential of bone tissue engineering using poly(lactide-co-glycolide)/hydroxyapatite (PLGA/ HAp) nanofibres, which is fabricated using electrospinning (Heo et al 2014;Lipner et al 2014;Haider et al 2015;Stachewicz et al 2015). However, the authors of these in vitro reports were unable to assess the biomechanical properties of the bone engineering processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bagian tulang sapi yang mempunyai kemiripan dengan tulang manusia dapat digunakan sebagai tulang pengganti, rekonstruksi tulang wajah, rekayasa jaringan, dan artifisial tulang [2].Kandungan tulang secara umum adalah 30 % organik dan 70 % inorganik [3] [4]. Kandungan inorganik pada tulang yang berisi 60 % hidroksiapatit (HA= Ca10(PO4)6(OH)2) [5] pada matriks kolagen, sedangkan komposisi HA tulang sapi 93 % dan 7% β-tricalcium phosphate (Ca3(PO4)2, β-TCP) [6]. Berdasarkan tinjauan kristalografi bahwaHidroksiapatit (HA) yang memiliki nilai perbandingan Ca/P sebesar 1,67 sangat stabil [2].…”
Section: Pendahuluanunclassified
“…Furthermore, composites of polymer/ceramic have been used to achieve appropriate properties. Many researches have used hydroxyapatite (HAp), the major material constituent of bone matrix, combining with polymers to improve their osteoconductivity [12], hydrophilicity [13], and mechanical behavior [2], also using for bone repair [14] and drug release applications [15].…”
Section: Introductionmentioning
confidence: 99%